2012
DOI: 10.1021/mz300135x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly Behavior of Thermoresponsive Oligo(ethylene glycol) Methacrylates Random Copolymer

Abstract: A well-defined random copolymer containing 2-(2-methoxyethoxy) ethyl methacrylate (MEO 2 MA, M n = 188 g/mol) and poly-(ethylene glycol) methyl ether methacrylate (PEGMA, M n = 2080 g/mol) (poly(MEO 2 MA-co-PEGMA 2080 )), M n = 17300 g/mol) was synthesized using the atom transfer radical polymerization (ATRP) process, and its thermoresponsive behaviors in aqueous solution were investigated. In comparison to other temperature-sensitive random copolymers based on oligo(ethylene glycol) methacrylates, this copoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 30 publications
4
51
0
Order By: Relevance
“…16 In this work, the authors take advantage of the relationship between oligoethylene glycol chain length and temperature sensitivity. Here, 2-(2-methoxyethoxy) ethyl methacrylate (MEO2MA) and poly(ethylene glycol) methyl ether methacrylate (PEGMA) copolymers were synthesized by ATRP.…”
Section: Physical-physical Dual Stimuli-responsive Macromoleculesmentioning
confidence: 99%
“…16 In this work, the authors take advantage of the relationship between oligoethylene glycol chain length and temperature sensitivity. Here, 2-(2-methoxyethoxy) ethyl methacrylate (MEO2MA) and poly(ethylene glycol) methyl ether methacrylate (PEGMA) copolymers were synthesized by ATRP.…”
Section: Physical-physical Dual Stimuli-responsive Macromoleculesmentioning
confidence: 99%
“…8,20,21 Unlike poly(ethylene glycol) (PEG), which can only be end-group functionalized, the free radical (co)polymerization method used to produce POEGMA enables the incorporation of a range of reactive comonomers or cross-linkers, facilitating production of pre-gel precursor polymers with a range of desired chemistries, cross-link densities, and molecular weights. We have previously reported extensively on modular POEGMA hydrogels cross-linked via hydrazone bonds, formed by reactive extrusion of aldehyde and hydrazide-functionalized precursor polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 28,29 ] Subsequently, a variety of polymer brushes, micelles, vesicles, micro/nanogels, as well as a few of smart hydrogels based on POEGMA have been developed in the past few years. [30][31][32][33] For instance, Huck and co-workers reported that surface attached P(MEO 2 MA -co-OEGMA) brushes exhibited a fast and reversible thermo-induced collapse transition, resulting in different surface properties of the polymer coating below and above the LCST. [ 34 ] Roth et al showed that POEGMA based copolymers also exhibit a UCST behavior in alcohol/ water mixtures.…”
Section: Introductionmentioning
confidence: 99%